Mutations in the A34R gene increase the immunogenicity of vaccinia virus - S. N. Shchelkunov; T. V. Bauer; S. N. Yakubitskiy; A. A. Sergeev; A. S. Kabanov; S. A. Pyankov (Вавиловский журнал генетики и селекции)
Vaccination is the most simple and reliable approach of protection to virus infections. The most effective agents are live vaccines, usually low-virulence organisms for humans and closely related to pathogenic viruses or attenuated as a result of mutations/deletions in the genome of pathogenic virus. Smallpox vaccination with live vaccinia virus (VACV) closely related to smallpox virus played a key role in the success of the global smallpox eradication program carried out under the World Health Organization auspices. As a result of the WHO decision as of 1980 to stop smallpox vaccination, humankind has lost immunity not only to smallpox, but also to other zoonotic, orthopoxviruscaused human infections. This new situation allows orthopoxviruses to circulate in the human population and, as a consequence, to alter several established concepts of the ecology and range of sensitive hosts for various orthopoxvirus species. Classic VACV-based live vaccine for vaccination against orthopoxvirus infections is out of the question, because it can cause severe side effects. Therefore, the development of new safe vaccines against orthopoxviral infections of humans and animals is an important problem. VACV attenuation by modern approaches carried out by targeted inactivation of certain virus genes and usually leads to a decrease in the effectiveness of VACV in vivo propagation. As a result, it can cause a diminishing of the immune response after administration of attenuated virus to patients at standard doses. The gene for thymidine kinase is frequently used for insertion/inactivation of foreign genes and it causes virus attenuation. In this research, the effect of the introduction of two point mutations into the A34R gene of attenuated strain LIVP-GFP (ТК–), which increase the yield of extracellular enveloped virions (EEV), on the pathogenicity and immunogenicity of VACV LIVP-GFP-A34R administered intranasally to laboratory mice were studied. It was shown that increase in EEV production by recombinant strain VACV LIVP-GFP-A34R does not change the attenuated phenotype characteristic of the parental strain LIVP-GFP, but causes a significantly larger production of VACV-specific antibodies.